La mode par ses métiers : histoire et savoir des fabricants du second xixe siècle - Émilie Hammen (In Situ)
During the second half of the 19thcentury, at a time when the creation and consumption of fashion were being invested by industry, it is possible to note an abundant production of texts seeking to analyse the history of fashion. But archaeologists and painters still concentrated primarily on the dress of the Ancien Régime, thought to be more interesting than contemporary clothing. The notion of haute couture and of its creators as a special breed of demiurges was still in its infancy. It was at this time then that some of the men with particular skills in the field, entrepreneurs and inventors, began to take up the historical narrative and to give contemporary fashion a past and a heritage. This article proposes a new examination of the issues and contexts that were specific to this literature by looking at three figures: Natalis Rondot, Auguste Dusautoy and Ernest Lefébure, associated, respectively, with the realms of textiles, clothing manufacturing and lacemaking. Drawing on their practical and theoretical skills, from museums to exhibitions of the industrial arts, what was the history of fashion they bequeathed to us? By looking at fashion through the prism of its trades, its materials, its gestures and its tools, a missing and so far little appreciated chapter in fashion historiography can be brought to life.